Characterization of a novel IncHI2 plasmid carrying tandem copies of blaCTX-M-2 in a fosA6-harboring Escherichia coli ST410 strain - Guo, Q; Ding, B; Jové, T; Stoesser, N; Cooper, V; Wang, M; Doi, Y (American Society for Microbiology, 2016)
Extended-spectrum β-lactamase gene blaCTX-M-2 is mainly associated with ISCR1 embedded in complex sul1-type integrons, but information on the genetic context of plasmids harboring the ISCR1-blaCTX-M-2module remains limited. In this study, a blaCTX-M-2-harboring plasmid pYD786-1 belonging to novel ST2-IncHI2 was sequenced and analyzed from an Escherichia coli ST410 clinical strain. pYD786-1 belonged to APEC-O1-R type IncHI2 plasmids which are widely distributed in human, poultry and livestock strains. It contained a multidrug resistance mosaic region (MRR) consisting of Tn21::In2 transposon backbone augmented by acquisition of duplicated ISCR1-blaCTX-M-2 Tn2411, a Tn21::In2 precursor, likely played a role in the generation of the MRR in pN13-01290_23, the putative progenitor plasmid of pYD786-1 found in a foodborne Salmonella strain. Tn21/Tn2411::In::ISCR1-blaCTX-M-2 derivatives including pYD786-1 have been identified in strains from Europe, South America and the U.S., suggesting potential global dissemination of the blaCTX-M-2 modules mediated by this vehicle.